Failure Criterion Evaluation of Unbound Granular Base Course - Siripun, Komsun; Jitsangiam, Peerapong; Nikraz, Hamid (International Committee on Road & Airfield Pavement Technology (ICPT), 2011)
This study aims to report theoretically the possible approach of confinement evaluation of unbound granular base course using the finite element method and laboratory results in order to implement current pavement material test algorithm. As is well known, triaxial and California bearing ratio (CBR) test are used to simulate the real condition of pavement materials under traffic loads by using static confinement and actuator loads. However static confining conditions in pavement structure occur only when no vehicle travels. As the effects of traffic loads and material attributes are generated when vehicles travel, horizontal stress and confinement behaviors of pavement structure were determined. CBR sample of crushed rock base was modeled using finite element in order to study the confining pressure behavior of such material subjected to applied stress. During the load application procedure, a single wheel with a standard pressure of 750 kPa was selected to compare with the analyzed strength of CRB based on laboratory test results.The results showed that horizontal stress of base course layer consists of overburdened soil and passive force from applied stress. When vehicle travels pass observed point, horizontal pressures of base course layer increase from overburdened weight and complete with passive force effect depend on applied stress and its internal friction. Seemingly, the conventional triaxial test results with finite element back calculation are able to describe the confining behavior of unbound granular base course. In this study, triaxial tests and the confinement evaluation using finite element approach on an unbound granular base course were introduced to explain and define its limited use in order to implement the current performance test of unbound granular base course material.